Relationship among team dynamics, care coordination and perception of safety culture in primary care. (18th May 2018) - Blumenthal, Karen J; Chien, Alyna T; Singer, Sara J
Abstract: Background: There remains a need to improve patient safety in primary care settings. Studies have demonstrated that creating high-performing teams can improve patient safety and encourage a safety culture within hospital settings, but little is known about this relationship in primary care. Objective: To examine how team dynamics relate to perceptions of safety culture in primary care and whether care coordination plays an intermediating role. Research Design: This is a cross-sectional survey study with 63% response ( n = 1082). Subjects: The study participants were attending clinicians, resident physicians and other staff who interacted with patients from 19 primary care practices affiliated with Harvard Medical School. Main Measures: Three domains corresponding with our main measures: team dynamics, care coordination and safety culture. All items were measured on a 5-point Likert scale. We used linear regression clustered by practice site to assess the relationship between team dynamics and perceptions of safety culture. We also performed a mediation analysis to determine the extent to which care coordination explains the relationship between perceptions of team dynamics and of safety culture. Results: For every 1-point increase in overall team dynamics, there was a 0.76-point increase in perception of safety culture [95% confidence interval (CI) 0.70–0.82, P < 0.001]. Care coordination mediated the relationship between team dynamics and the perception of safety culture. Conclusion: Our findings suggest there is a relationship between team dynamics, care coordination and perceptions of patient safety in a primary care setting. To make patients safer, we may need to pay more attention to how primary care providers work together to coordinate care.